Prevalence of Lip and Palate Clefts and the Related Factors in Babies Born From 2014 to 2019 in Karaj, Iran - faraz farahi Araghi; Seyed Mostafa Mortazavi; Samar Esmaeili; Masoumeh Esmaily (مجله دانشگاه علوم پزشکی گیلان)
Background: Cleft lip and palate are the most common congenital anomalies in the head and neck region, which are affected by environmental and genetic factors. These defects can cause serious problems such as deformity, nutritional, respiratory and social interactions for patients. Objective: The current study was performed to investigate the frequency of cleft lip and palate and its related factors in infants born in Karaj’s hospitals during 2014 to 2018. Methods: This descriptive-analytical study was conducted on the case of newborns. The studied population included 91,563 cases of babies born between 1993 and 1997 in Kamali, Imam Ali (AS), Maryam and Qaim hospitals in Karaj. Of these, 46 babies were identified with various types of oral clefts. The information of the files was collected and analyzed with SPSS v24 statistical software.. Results: The prevalence of oral cleft was 0.5 per thousand live births. (26.08%) of infants had cleft lip, (52.17%) cleft palate, and (21.73%) cleft lip and palate (P = 0.024). 56.52% of male babies (P = 0.37), 76.08% of mothers in the age group of 20 to 30 years with an average age of 24.4 years, 58.69% of first pregnancy mothers, 13.03% of parents, history Family marriage (P< 0.001), and 37% of mothers had blood type A in the file (P = 0.11). Conclusion: The prevalence of oral clefts in Karaj is lower than the global statistics and other regions of the country.